2023
DOI: 10.1111/jvh.13837
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of reported hepatitis C diagnoses from 1998 to 2018 in immigrants and nonimmigrants in Quebec, Canada

Abstract: Immigrants living in low hepatitis C (HCV) prevalence countries bear a disproportionate HCV burden, but there are limited HCV population-based studies focussed on this population. We estimated rates and trends of reported HCV diagnoses over a 20-year period in Quebec, Canada, to investigate subgroups with the highest rates and changes over time. A population-based cohort of all reported HCV diagnoses in Quebec (1998-2018) linked to health administrative and immigration databases. HCV rates, rate ratios (RR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Disparities remained among the immigrant subgroups in our study, however, as those born prior to 1945 were less likely to receive RNA testing relative to the younger immigrants, and immigrants from Latin America and the Caribbean were less likely to receive RNA testing and treatment compared to immigrants from high-income regions. Long delays in diagnosis and treatment resulting from a lack of systematic screening after arrival in Canada [ 46 ], coupled with unique barriers to accessing and navigating healthcare after immigration, make this group a particularly vulnerable and at-risk group for end-stage liver disease (ESLD). Studies in the pre-DAA era demonstrated a higher risk of developing HCC and dying in hospital due to liver-related complications among immigrants compared to those born in Canada [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disparities remained among the immigrant subgroups in our study, however, as those born prior to 1945 were less likely to receive RNA testing relative to the younger immigrants, and immigrants from Latin America and the Caribbean were less likely to receive RNA testing and treatment compared to immigrants from high-income regions. Long delays in diagnosis and treatment resulting from a lack of systematic screening after arrival in Canada [ 46 ], coupled with unique barriers to accessing and navigating healthcare after immigration, make this group a particularly vulnerable and at-risk group for end-stage liver disease (ESLD). Studies in the pre-DAA era demonstrated a higher risk of developing HCC and dying in hospital due to liver-related complications among immigrants compared to those born in Canada [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a population‐based cohort of all laboratory‐confirmed hepatitis C diagnoses in Quebec, between 1990 and 2018, was obtained from the reportable disease database (MADO) or the Quebec Public Health Laboratory (LSPQ), linked to several provincial administrative data sets. The reported cases with HCV were linked to the provincial health insurance registry (FIPA) databases using a unique health care number 12 . The sources of CHC case definition for retrospective analysis of BC, Ontario and Quebec are given in Hamadeh et al 13 …”
Section: Methodsmentioning
confidence: 99%
“…From the health administrative data for BC, Ontario and Quebec, we extracted the annual incidence of newly diagnosed hepatocellular carcinoma (HCC), decompensated cirrhosis (DC), confirmed CHC cases as well as HCV treatment initiations for the three birth cohorts from 2000 to 2018. DC and HCC diagnosis codes were defined based on previously published studies 12–15 …”
Section: Methodsmentioning
confidence: 99%